Remote Router Access Protocols: Security Implications of TELNET and SSH (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract - A key component in current network administration is remote access to network devices, which helps effective management and troubleshooting. TELNET and Secure Shell (SSH), two of the protocols that provide this kind of access, are widely used for their functions in router setup and upkeep. The security implications of remote router access via TELNET and SSH are critically examined in this work. Due to its early architecture and lack of encryption, TELNET makes network traffic extremely vulnerable to eavesdropping in modern settings. On the other hand, SSH improves the secrecy and integrity of data by providing secure communication channels and strong authentication.